Direct synchronous-asynchronous conversion system for hybrid electrical vehicle applications. An energy-based modeling approach - Muñoz Aguilar, Raul S (2012)
This paper presents a proposal for a series hybrid electric vehicle propulsion system. This new configuration is based on a wound-rotor synchronous generator (WRSM) and a doubly-fed induction machine (DFIM). The energy-based model of the whole system is obtained taking advantage of the capabilities of the port-based modeling techniques. From the dq port-controlled Hamiltonian description of the WRSM and DFIM, the Hamiltonian model of the proposed Direct Synchronous-Asynchronous Conversion System (DiSAC) is developed. Subsequently, the bond graph models of the DiSAC and associate systems are also provided. Numerical simulations are also presented in order to validate the proposed system.